Analisis Destination Branding Kawasan Wisata Taman Sari melalui Metode Importance Performance Analysis - Novi Irawati; Sabda Elisa Priyanto; Yuliana Pinaringsih Kristiutami (Media Wisata, 2019)
Taman Sari Tourism Marketing Strategy Through Destination branding has tourism potential through culture and historical value. With this potential, the government is managing tourism in order to be able to move the economy in Taman Sari. In realizing this vision, planning and strategy are needed, one of which is Destination Branding. Destination branding is used in every tourism site in the world and is able to make a good impact on the progress of tourism, for example, are the Twin Towers in Malaysia, the Merlion Statue in Singapore, the Taj Mahal in India, etc. Destination branding has an important role to be able to increase the number of tourist visits. This study uses a qualitative approach, a qualitative approach is used in order to get complete information about tourism marketing strategies with Destination Branding. The results of this study found that the Destination branding strategy in Taman Sari is not planned systematically so that Destination branding is only understood in a small way, that is only in the visualization aspect. So that tourism product development programs are not in accordance with the concept of Destination branding that has been made